The Influence of Product Quality, Prices and Promotions on Customer Loyalty UD. Setya Abadi D.M - ANIKAWATI, Vika; HARIYANA, Nanik (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: In today's competitive business era, maintaining customer loyalty is one of the critical factors for the long-term success of a company. This research aims to determine the impact of product quality, Price, and promotion on customer loyalty. This research was conducted at UD. Setya Abadi D.M in October 2023.Methodology:The method used is a quantitative study using primary data. Primary data was obtained from research participants through online Google forms and questionnaires. The population in this study were all buyers of UD. Setya Abadi D.M. This research uses 12 indicators, so the test estimate is 75-150. Based on these considerations, the test size for this research was set at 100 respondents.Findings: Based on the research conducted, the conclusion of this research states that product quality has a significant influence on customer loyalty. It means that the higher the quality of the product, the greater the consumer's loyalty to the product.Implication:Price has an essential impact on customer loyalty. It means that the higher the product price, the higher the consumer's dependence on that product. Promotion has an essential impact on customer loyalty. It means that the better the promotion, the higher the customer loyalty.